KELAYAKAN MEDIA PAPAN KONVERSI SATUAN BAKU UNTUK SISWA KELAS III SEKOLAH DASAR - Ilham Wahyu, Halindra; Rarasati, Ida Putri; Malahayati, Eva Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The results of observations, interviews, and a student needs questionnaire conducted at the Ngadipuro 03 Elementary School and Ngeni 04 Elementary School units served as the basis for the researchers' identification of issues related to the lack of available learning media on the basic concepts of standard units. Learning media related to the basic concepts of standard units still utilizes the unit ladder outlined in textbooks. Determining the feasibility of the media was the objective of this study. The media was a standard unit conversion board developed for third-grade elementary school students. Research and Development (R&D), limited to the product trial and revision stages, served as the research method. Data collection tools included questionnaires for validation by material, media, and language experts, as well as questionnaires for teacher and student readability. The validation questionnaire results showed a feasibility score from the material expert of 88%, media expert 82%, and language expert 83%. The results validated by these three experts were categorized as very feasible. The student readability questionnaire achieved a 95% score, and the teacher readability questionnaire achieved a 96% score. Both questionnaire results were in the very appropriate category. Therefore, the standard unit conversion board is suitable for teaching mathematics in elementary schools.